Schizophrenia, substance abuse, and violent crime. - Fazel, S; Långström, N; Hjern, A; Grann, M; Lichtenstein, P (2009)
CONTEXT: Persons with schizophrenia are thought to be at increased risk of committing violent crime 4 to 6 times the level of general population individuals without this disorder. However, risk estimates vary substantially across studies, and considerable uncertainty exists as to what mediates this elevated risk. Despite this uncertainty, current guidelines recommend that violence risk assessment should be conducted for all patients with schizophrenia. OBJECTIVE: To determine the risk of violent crime among patients diagnosed as having schizophrenia and the role of substance abuse in mediating this risk. DESIGN, SETTING, AND PARTICIPANTS: Longitudinal designs were used to link data from nationwide Swedish registers of hospital admissions and criminal convictions in 1973-2006. Risk of violent crime in patients after diagnosis of schizophrenia (n = 8003) was compared with that among general population controls (n = 80 025). Potential confounders (age, sex, income, and marital and immigrant status) and mediators (substance abuse comorbidity) were measured at baseline. To study familial confounding, we also investigated risk of violence among unaffected siblings (n = 8123) of patients with schizophrenia. Information on treatment was not available. MAIN OUTCOME MEASURE: Violent crime (any criminal conviction for homicide, assault, robbery, arson, any sexual offense, illegal threats, or intimidation). RESULTS: In patients with schizophrenia, 1054 (13.2%) had at least 1 violent offense compared with 4276 (5.3%) of general population controls (adjusted odds ratio [OR], 2.0; 95% confidence interval [CI], 1.8-2.2). The risk was mostly confined to patients with substance abuse comorbidity (of whom 27.6% committed an offense), yielding an increased risk of violent crime among such patients (adjusted OR, 4.4; 95% CI, 3.9-5.0), whereas the risk increase was small in schizophrenia patients without substance abuse comorbidity (8.5% of whom had at least 1 violent offense; adjusted OR, 1.2; 95% CI, 1.1-1.4; P<.001 for interaction). The risk increase among those with substance abuse comorbidity was significantly less pronounced when unaffected siblings were used as controls (28.3% of those with schizophrenia had a violent offense compared with 17.9% of their unaffected siblings; adjusted OR, 1.8; 95% CI, 1.4-2.4; P<.001 for interaction), suggesting significant familial (genetic or early environmental) confounding of the association between schizophrenia and violence. CONCLUSIONS: Schizophrenia was associated with an increased risk of violent crime in this longitudinal study. This association was attenuated by adjustment for substance abuse, suggesting a mediating effect. The role of risk assessment, management, and treatment in individuals with comorbidity needs further examination.